Microcystin concentrations in Nile tilapia (Oreochromis niloticus) caught from Murchison Bay, Lake Victoria and Lake Mburo: Uganda - Semyalo, Ronald; Rohrlack, Thomas; Naggawa, Christine; Nyakairu, George W. (Hydrobiologia, 2010)
Catches of the economically important Nile tilapia (Oreochromis niloticus L.) from two eutrophic tropical lakes in Uganda, Lake Mburo and Murchison Bay, Lake Victoria, were examined to determine the presence of microcystins (MCs) in gut, liver and muscle of the fish. Analysis for MCs (RR, LR and YR) in both fish and water samples was by liquid chromatography coupled with mass spectroscopy (LC-MS) method. Physico-chemical parameters were also measured to establish the status of both lakes. MC-RR was the most prominent MC detected in Lake Mburo and Murchison Bay samples, there was no evidence of significant seasonal variation in the concentration of MCs in fish tissue. MCs were detected in all water samples from both study lakes. The mean concentration of MCs in water was found higher in dry times for Lake Mburo (P\0.05) and higher in wet times for Murchison Bay (P\0.05). MC concentrations in the fish guts were positively related with MC concentrations in water samples from Murchison bay (P\0.05), no such correlation was found in Lake Mburo. In eutrophic tropical lakes, fish seem to have a high tolerance to the toxicity of cyanotoxins including MCs. However, there is a possibility of accumulating these toxins in their tissue with the threat of transferring them higher up in the food chain. Due to a low sample size and short sampling period, the results can only serve to highlight the potential risk of MC accumulation in Nile tilapia in these lakes. Further studies are needed for the purpose of risk assessment.
Keywords: Microcystins; Lake Victoria; Lake Mburo; Nile tilapia